Using Illustrated Stories to Improve Reading Comprehension: Evidence from Junior High School Students in Indonesia - Miftahul Jannah; Jufriadi Jufriadi; Husnaini Husnaini (Faculty of Education and Teacher Training of UIN Palopo, 2025)
Reading comprehension plays a crucial role in English language learning, yet many junior high school students in Indonesia struggle to understand English texts due to limited vocabulary and low motivation. To address these challenges, this study investigated the effectiveness of illustrated stories as a medium to enhance students’ reading comprehension. The research employed a pre-experimental design using a one-group pre-test and post-test model. The participants were 25 eighth-grade students of SMPN 08 Palopo, selected purposively based on their low proficiency in reading English texts. The instrument consisted of a reading comprehension test, while the treatment involved five sessions of instruction using illustrated stories covering different types of narrative texts. The findings revealed that the mean score of students improved from 38.36 in the pre-test to 61.40 in the post-test. The paired sample t-test result (t = -5.253, p < 0.001) indicated a statistically significant difference between the two sets of scores, confirming the effectiveness of illustrated stories in improving reading comprehension. Furthermore, the post-test classification showed that more students achieved the good and very good categories compared to the pre-test, where the majority were in the poor and very poor categories. These results suggest that illustrated stories provide both cognitive and motivational benefits by integrating textual and visual elements that make reading more engaging and accessible. The study concludes that illustrated stories are an effective medium for teaching reading comprehension and recommends their integration into English as a Foreign Language (EFL) classrooms at the junior high school level.